2019
DOI: 10.1155/2019/9516981
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Substances Produced by NativeLactobacillus plantarumUTNCys5-4 Control Microbial Population Growth in Meat

Abstract: Microbial contamination is the cause of extensive economic loss in the food sector. Previously, the wide-range antimicrobial capacity of inhibitory substances secreted by the Lactobacillus plantarum UTNCys5-4 strain was demonstrated in vitro; however, its mechanism of action in the food matrix remains unclear. This study was aimed to evaluate the effect of antimicrobials produced by the Cys5-4 strain in raw meat applied as pure cell cultures, cell-free supernatant (CFS), and partially purified peptides. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…No DNA/RNA was detected in untreated control samples. This result was in agreement with our previous findings that some peptides disrupt the cell membrane of the target Gram-negative bacteria and their effectiveness was target specific ( Tenea and Guana, 2019 ). Recent work on the synthetic peptide melamine mode of action against S. aureus indicates that the peptide interacted with the target cell membrane inducing membrane depolarization and leakage of ATP and DNA/RNA molecules followed by cell death, whereas another protein Mel4 does not induce cell membrane disruption inducing cell killing by autolysis mechanism ( Yasir et al, 2019 ).…”
Section: Resultssupporting
confidence: 93%
“…No DNA/RNA was detected in untreated control samples. This result was in agreement with our previous findings that some peptides disrupt the cell membrane of the target Gram-negative bacteria and their effectiveness was target specific ( Tenea and Guana, 2019 ). Recent work on the synthetic peptide melamine mode of action against S. aureus indicates that the peptide interacted with the target cell membrane inducing membrane depolarization and leakage of ATP and DNA/RNA molecules followed by cell death, whereas another protein Mel4 does not induce cell membrane disruption inducing cell killing by autolysis mechanism ( Yasir et al, 2019 ).…”
Section: Resultssupporting
confidence: 93%
“…No ghost cells were detected, indicating that the morphological and ultrastructural changes may rely not only on the concentration and exposure time but also on the identity (origin) of the antimicrobial agent. This mechanism might be explained by the differences in the peptide mixture produced by the Gt2 and Cys5-4 strains; Gt2 has four products of approximately 22, 32, 35, and 55 kDa, while Cys5-4 produces peptides of 10, 15, 20, and 30 kDa [ 15 , 16 ]. However, more than one peptide or protein-like agent is responsible for the overall antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Early research indicated that the treatment of Salmonella enterica ATCC51741 at both the vegetative and exponential phases of growth with the cell-free supernatant of Gt28 resulted in complete inactivation upon 3 h, suggesting its bactericidal mode of action [ 14 ]. Contrary to Gt2 and Cys5-4 peptide extracts containing a mixture of low- and larger weight peptides [ 15 , 16 ], peptide extract from Gt28 contained one peptide of 15 kDa and some extra larger peptides or protein-like products as deducted in SDS-PAGE, but further analysis is required to detect the extract composition (Figure S2 ). The cell membrane showed interrupted stretches, and electron-dense material accumulated in the periplasmic space ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tenea and co-workers investigated the mechanism by which Gt2 peptides and Cys5-4 peptides, from L. plantarum UTNGt2 and UTNCys5-4, respectively, target Gram-negative bacteria ( Table 1 ). Gt2 and Cys5-4 peptides comprise, in turn, two or more post-translationally modified peptides forming one aggregate forming one functional inhibitory unit, which altered the cellular membrane permeability of E. coli and Salmonella , causing the leakage of cytoplasmic contents, followed by cellular death [ 50 , 51 ]. In a later study, the same authors investigated deeply the changes in Salmonella cells treated with Gt2 and Cys5-4 extracts, highlighting the occurrence of direct interaction between Salmonella genomic DNA and the peptides [ 46 ].…”
Section: Nature and Mechanisms Of L Plantarum Antimicrobialsmentioning
confidence: 99%
“…Plantaricins (especially Q7 [ 121 ], NC8 [ 122 ], Gt2 peptides and Cys5-4 peptide [ 46 , 51 ], IIA-1A5 [ 123 ], KL-1Y [ 58 ], ZJ316 [ 124 ], plantaricin 3, 5 [ 48 ]) are very active against Salmonella spp., a Gram-negative bacterium including pathotypes such as Salmonella enterica subspecies ( S. enteritidis ) and Salmonella enterica serotypes ( S. typhimurium ) ( Table 1 ). Both can cause severe illnesses, ranging from gastroenteritis to typhoid (Typhi) and paratyphoid fever (Paratyphi), a global problem with more than 27 million cases worldwide each year [ 125 , 126 ].…”
Section: Antibacterial and Antiviral Spectrum Of L Plantarum Extracellular Compoundsmentioning
confidence: 99%